ANALISIS PENGARUH MANAJEMEN MODAL KERJA DAN PERTUMBUHAN PENJUALAN TERHADAP PROFITABILITAS PADA PT DELTASINDO SAGITA MANDIRI - Didi Chandra; Tri Apriyono (Unit Pengelola dan Pengembangan Jurnal Ilmiah dan Informasi (UPPJII) STIE Jambatan Bulan, 2021)
This study aims to determine the effect of working capital management and sales growth on profitability at PT Deltasindo Sagita Mandiri. This research is an associative type of research using multiple linear regression analysis tools and classical assumption test using SPSS software. This research was conducted at PT Deltasindo Sagita Mandiri Mimika Regency with data for 8 (eight) periods starting from 2012 to 2019. Data collection techniques were carried out using interviews and literature studies. The results of the study conclude that sales growth (SG) has no significant effect on profitability. Meanwhile, working capital management which is proxied into the Cash Conversion Cycle (CCC) has a significant effect on profitability at PT Deltasindo Sagita Mandiri.